Stay Fresh, Stay Hydrated : Pemberdayaan Remaja Dalam Manajemen Hidrasi Melalui Self-Management” - TRIWIJAYANTI, RENNY (IKesT Muhammadiyah Palembang, 2025)
Abstract Background: Dehydration is a common problem in adolescents due to lack of awareness of the importance of adequate hydration. Poor hydration habits can affect health and concentration in learning. The self-management approach is an effective solution to encourage adolescents to manage their hydration habits independently, by building awareness and responsibility in maintaining daily fluid intake. Objective: This community service activity aims to improve the understanding and awareness of students of SMP Muhammadiyah 6 Palembang regarding the importance of adequate hydration for health through interactive education based on self-management. Method: This activity includes the stages of licensing, preparation, implementation, and evaluation. Education is provided interactively through discussions, simulations, and educational games. Evaluation is carried out by comparing the results of the pre-test and post-test to measure the increase in student understanding. Results: The evaluation results showed a significant increase in student understanding regarding hydration. In addition, there were positive behavioral changes, such as bringing a water bottle to school and setting reminders to drink water. However, challenges such as old habits that are difficult to change still need to be overcome through ongoing education. Conclusion: Interactive education based on self-management has proven effective in improving students' understanding and awareness of hydration. The sustainability of the program can be supported by the provision of drinking water facilities in schools and collaboration with medical personnel or nutritionists. Keywords: hydration, adolescents, self-management